The A-10 Thunderbolt - Hansen, Ole Steen; Pang, Alex (Mankato, Minn. : Capstone Press, 2006)
"An in-depth look at the A-10 Thunderbolt, with detailed cross-section diagrams, action photos, and fascinating facts"--Provided by publisher.
8 - 14 years
Keywords: A-10 (Jet attack plane); Airplanes, Military -- United States